The impact of wheelchair rugby classification line-up structure on possession outcome - Quinn, L. O.; Bruce, L. M.; Young, C. M. (Journal of Science and Medicine in Sport, 2024)
Objectives To investigate the impact that the structure and combination of athlete classification within line-ups has on possession outcome in Wheelchair Rugby (WR). Design. Retrospective.